Development and laboratory evaluation of a self-monitoring polymer geobelts. (15th December 2020) - Zhang, Jiong; She, Rui; Xia, Shuang; Dai, Zhaoxia; Hu, Nian; Cui, Xinzhuang; Han, Ruonan; Ming, Ruiping; Ma, Guodong
Graphical abstract: In this study, a self-monitoring polymer geobelt manufactured via 3D printing technology is proposed; conductive acrylonitrile–butadienestyrene (ABS) was embedded directly into non-conductive polylactic-acid (PLA) in the form of a conductive wire. The self-monitoring polymer geobelt made of PLA and conductive ABS presented good self-perception characteristics and recoverability; the higher the number of internal conductive wires arranged in a longitudinal layout, the more accurate the results. The relationship between the resistance and the tensile stress after being normalized at the ends of the geobelt can be fitted using the parabola f = A + Br + Cr 2, and the strain of the smart geobelt ranged from 2.1 to 10%. Highlights: A sealed self-monitoring polymer geobelt is proposed. Geobelt is made up by conductive core and nonconductive coating material. 3D printing reduces the time of specimen preparing and improves the repeatability. Abstract: Due to the rise of smart city construction in recent years, there is a growing demand for materials that can both improve the mechanical properties of structures and carry out health monitoring and risk warning. In this paper, a self-monitoring polymer geobelt manufactured by 3D printing technology is proposed, which can embed conductive ABS material directly into non-conductive PLA material as conductive wire. This integrated resistance geobelt solves the problem of sensor contact to the outside of the grid and water which is easy to fall off and the test results are inaccurate. In this study, a series of tests were performed to study the development and laboratory evaluation of a tensoresistivity geobelts and conclusions were drawn as follows: The self-monitoring polymer geobelt made with PLA and conductive ABS showed good self-perception characteristics and recoverability, and the more the number of longitudinal layout of internal conductive wires, the more accurate the results showed. The relationship between resistance and tensile stress after normalized at ends of the geobelt can be fitted by parabola f = A + Br + Cr 2, and the strain of smart geobelt ranges from 2.1 to 10%.